INFORMATION SUBSIDY DURING THE PANDEMIC: a case in Indonesian journalism - Aisyah, Vinisa Nurul; Anggoro, Dimas Aryo (Brazilian journalism research, 2024)
ABSTRACT – This research analyzes the subsidy information during the covid-19 pandemic from the Indonesian Government’s press release to mass media news. Information subsidies are a compelling practice to study since they describe how information flows in society. This practice becomes unavoidable, especially during the pandemic, which implies restrictions on activities and social distancing. This research used framing analysis and quantitative methods. The results indicated practices of information subsidies with a total of 95.65% from the Indonesian government press release samples published by mass media in the form of news in the same period. The analysis showed no significant difference between information from government press releases and news on detik.com through analysis of dominant frame, episodic and thematic framing, emotional appeal, gain-loss framing, sourcing news, and news tone. It is feared that the practice of information subsidies will lead to the degeneration of social responsibility from the mass media and eliminate the data verification process in journalism. RESUMO – Esta pesquisa analisa as informações sobre subsídios durante a pandemia da covid-19, desde o comunicado de imprensa do governo indonésio até as notícias da mídia de massa. Os subsídios de informações são uma prática interessante a ser estudada, pois descrevem como as informações fluem na sociedade. Essa prática se torna inevitável, especialmente durante a pandemia, o que implica restrições às atividades e distanciamento social. Esta pesquisa utilizou análise de enquadramento e métodos quantitativos. Os resultados indicaram práticas de subsídios de informação com um total de 95.65% das amostras de comunicados de imprensa do governo indonésio publicados pela mídia de massa na forma de notícias no mesmo período. A análise não mostrou diferença significativa entre as informações dos comunicados de imprensa do governo e as notícias no site detik.com por meio da análise do enquadramento dominante, enquadramento episódico e temático, apelo emocional, enquadramento de ganho-perda, notícias de origem e tom das notícias. Teme-se que a prática de subsídios de informação leve à degeneração da responsabilidade social da mídia de massa e elimine o processo de verificação de dados no jornalismo. RESUMEN – Esta investigación analiza la información subvencionada durante la pandemia de covid-19, desde el comunicado de prensa del Gobierno indonesio hasta las noticias de los medios de comunicación. Las subvenciones a la información son una práctica interesante de estudiar, ya que describen cómo fluye la información en la sociedad. Esta práctica se hace inevitable, especialmente durante la pandemia, lo que implica restricciones en las actividades y distanciamiento social. Esta investigación utilizó análisis de encuadre y métodos cuantitativos. Los resultados indicaron prácticas de subvención de la información con un total del 95.65% de las muestras de comunicados de prensa del gobierno indonesio publicados por los medios de comunicación en forma de noticias en el mismo periodo. El análisis no mostró diferencias significativas entre la información de los comunicados de prensa del gobierno y las noticias de detik.com mediante el análisis del encuadre dominante, el encuadre episódico y temático, el atractivo emocional, el encuadre de ganancia-pérdida, las noticias de origen y el tono de las noticias. Se teme que la práctica de las subvenciones a la información provoque la degeneración de la responsabilidad social de los medios de comunicación y elimine el proceso de verificación de datos en el periodismo.